2019
DOI: 10.1371/journal.pone.0220204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tobacco smoking on the risk of developing community acquired pneumonia: A systematic review and meta-analysis

Abstract: Aim To summarise and quantify the effect of tobacco smoking on the risk of developing community acquired pneumonia (CAP) in adults. Methods We systematically searched MEDLINE, Embase, CINAHL, PsychINFO and Web of Science, from inception to October 2017, to identify case-control and cohort studies and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist. The review protocol was registered with the PROSPERO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
2
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 46 publications
5
72
2
2
Order By: Relevance
“…In the CAP population, smoking increases the risk of 30-day mortality independently of tobacco-related comorbidity and age. A recently published systematic review reported that tobacco smoke exposure is significantly associated with the development of CAP in both current and ex-smokers and that passive smokers aged >65 years are at higher risk of CAP [71].…”
Section: The Role Of Pneumonia and Secondary Bacterial Infection In Tmentioning
confidence: 99%
“…In the CAP population, smoking increases the risk of 30-day mortality independently of tobacco-related comorbidity and age. A recently published systematic review reported that tobacco smoke exposure is significantly associated with the development of CAP in both current and ex-smokers and that passive smokers aged >65 years are at higher risk of CAP [71].…”
Section: The Role Of Pneumonia and Secondary Bacterial Infection In Tmentioning
confidence: 99%
“…A recent meta-analysis including 7 studies also revealed that smokers have a double risk of severe COVID-19 (pooled OR=1.98; 95% CI: 1.29-3.05) 8 . A meta-analysis published in 2019 including 27 studies and 460592 participants revealed current smokers (pooled OR=2.17; 95% CI: 1.70-2.76) and ex-smokers (pooled OR=1.49; 95% CI: 1.26-1.75) were more likely to develop community-acquired pneumonia compared to never smokers 9 . The evidence suggests that smokers are more vulnerable to lung infection, and COVID-19 is no exception.…”
mentioning
confidence: 99%
“…34 In the case of all-cause CAP, a recent systematic review and meta-analysis, encompassing 27 studies and 460,592 participants, revealed that current smokers have a significantly increased risk for development of CAP relative to never-smokers (OR 2.17; 95% CI, 1.70-2.76, n ¼ 13 studies). 35 Passive smoking is associated with a 64% increase in the risk for development of CAP, but only for those aged >65 years (OR 1.64; 95% CI, 1.17-2.30, n ¼ 2 studies). 35 Smoking-related increased susceptibility for development of severe pneumococcal disease has generally been attributed to cigarette smoke-mediated suppression of innate and adaptive pulmonary host defenses.…”
Section: Smokingmentioning
confidence: 93%
“…35 Passive smoking is associated with a 64% increase in the risk for development of CAP, but only for those aged >65 years (OR 1.64; 95% CI, 1.17-2.30, n ¼ 2 studies). 35 Smoking-related increased susceptibility for development of severe pneumococcal disease has generally been attributed to cigarette smoke-mediated suppression of innate and adaptive pulmonary host defenses. 36 Our research findings, some very recent, have, however, revealed additional pathogentargeted mechanisms that are likely to contribute to smoking-related susceptibility for development of severe pneumococcal disease.…”
Section: Smokingmentioning
confidence: 93%